Hubungan Kuliah Kerja Nyata dan Kemandirian Masyarakat Dengan Keberhasilan Pembangunan Desa - Mawardiningsih, Wahjoe (Universitas Surakarta, 2010)
Abstract Lifts research problem about the relation of Kuliah Kerja Nyata and independence of public with success of development of countryside, be idea from research to know are there relation between Kuliah Kerja Nyata and independence of public with Development Success of Countryside. Writer wish to know are there difference of the relation of Kuliah Kerja Nyata and independence of public which different of while from this research found that independence of high public has contribution which positive to the relation of Kuliah Kerja Nyata with Development of Countryside. On the contrary independence of public that is low relative of its the contribution haves the character of negativity to the relation of Kuliah Kerja Nyata with Development of Countryside. Hereinafter from comparison difference test of there is no a marked difference about perception of public to program Kuliah Kerja Nyata from countryside with level of high independence, and also countryside with level of lower independence. Keyword: pembangunan, kemandirian desa.